Etno-ornitologia no entorno do Parque Nacional de Sete Cidades, Piauí, Brasil - Alves, Isis Tamara Lopes de Sousa (2019)
Interactions between the various human groups and natural resources have resulted in relevant relationships for society, since the environment for some people portrays an area of appreciation, knowledge and learning. Many species of wild birds are used for different purposes in Brazil, such as pets, traditional medicine, food (meat, eggs, bones), illegal trade, religious rituals, ornamentation, and pleasure and companionship. Therefore, Ethno-ornithology seeks to understand and analyze the relationships between humans and birds, practices, symbolism, meaning and use of these animals by people. This work had as objective to inventory the known bird species and their uses, by residents of the community Cachoeira in the neighborhood of the PARNA of Sete Cidades, Piauí, Brazil. It is estimated that the richness of bird species known to local people can give an indication of which species are available in the environment, as well as which of them has been under use pressure. Data were collected through interviews with semi-structured forms and informal conversations, addressing several aspects of birds known in the region. The identification of the species found was performed through the direct visualization of the species during the interviews, through photos and based on previous studies in the research area. We had the participation of 31 informants, heads of household (men and / or women). We recorded a total of 86 species, distributed in 74 genera and 33 families. The families Columbidae, Thraupidae, Accipitridae and Icteridae were highlighted with the largest number of species mentioned. Regarding the categories of bird use, the informants demonstrated knowledge regarding 4 different types: food (N = 48 species), breeding as pets (N = 37), magico-religious (N = 6) and or medicinal (N = 5). In relation to the abundance of the species, Penelope superciliaris stands out as the least found species in the region, presenting relevant percentages of rare and low abundance. In this way, it was possible to observe the wide knowledge of the residents of the community Cachoeira, not only the richness of species but also the different types of use of these animals. In the same way, we analyze the importance of Conservation Units in the maintenance of bird life, since some of them, such as jacú, have been found easily in the internal areas of this unit, while the residents claim not to see them near their homes , indicating that these animals may associate these units as a safe and sheltered place.